Prinsip Tanggung Gugat Dari Profesi Perencana terhadap Kegagalan Pekerjaan Jasa Konstruksi Jalan Tol - Purwadi, Ari (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract. The existence of the Indonesia Toll Road Authority, the authority in charge of the implementation of toll roads in Indonesia is expected to promote the establishment of the acceleration of the implementation of the toll road involving business entities. Binding of construction employment between users and providers of construction services construction services performed by establishing a construction contract. Issues that arise in the construction planner service is legal responsibilities as a professional on quality service their professionalism. This legal research using statute approach and the conceptual approach. Characteristics of the concession is a government contract, the contract between Indonesia Government and the toll road business entities, so that the relations with the toll road business entities are private relationship. The use of freedom of contract principle in government contracts has been limited, namely in government procurement auctions work done through toll road engineering planning services, where tender documents are included in the contract document, as it relates to toll road infrastructure with investments that very large to serve the public interest. Professional responsibility in the form of consulting the profession is responsibility based on profession standards (professional ethics), liability under the law, and responsibility based on scientific techniques standards. Responsibility based on scientific technique standards involves the government to form a team of experts in determining whether there is fault or not fault on consulting services. Legal liability using liability based on fault. In order to balance the elements of proof fault, it is advisable to revise the rules of the principle liability based on fault become presumption of liability principle.Keywords : liability, planners, toll road, building failures, failures construction .Â